Impact of Implementing Faith Deepening Activities Regarding the People's Experience of Faith in The Parish of Santa Maria Bunda Para Bangsa Gunungsitoli-Nias - Harefa, Evimawati (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Considering that the basic mission of the Church is to be a servant of the Word, efforts to proclaim and realize a contextual Gospel in society must also pay attention to existing concrete situations and needs. The aim of this research is to find out faith deepening activities, the meaning of the appreciation of faith and its benchmarks, the influence of faith deepening activities on the people's appreciation of faith. In this paper the author uses quantitative research methods. In collecting data, the author distributed an open questionnaire (a questionnaire that has questions in the form of questions, with answer choices such as; very often, often, quite often, never, and several other alternative answers that have the same score (in the form of multiple choices), The assessment scale given to research subjects was measured using a Likert scale. The results of the multicollinearity test, the author found that the sub-variable of faith deepening activities (X) which had a very good effect on the variable of people's appreciation of faith (Y) was the implementation time sub-variable (X1), namely with The calculated t value is 2.953, while the sub-variable of materials used (X2) and the method sub-variable (X3) have a good effect and the faith building sub-variable (X4) has quite a good effect. The conclusion of this research is that there is an influence of the implementation of faith deepening on appreciation the faith of the people in the St. Maria BPB Gunungsitoli-Nias parish, Sibolga Diocese.